Da Oralidade à Escrita: uma leitura semiótica de narrativas tradicionais populares. - Lima Filho, Jailto Luis Chaves de (2013)
The traditional popular roman is very alike with the cordel leaflet. The lacks between both are highlighted by some expertise with respect to the linguistic code one made use of, which is oral for the popular roman and written for the cordel. Alike the oral Roman, other pieces of work are also traditional throughout generations kept by poets memories. However, by reading a cordel novel or an oral roman one observes some important structural differences among them which are the purpose of this paper. On being so, the aim of this study is to characterize two popular plays by considering their discursive features in order to draw a comparative analysis in similitude and difference. As theoretical basis, one considered the updated models offered by the Greimasian Semiotics, more specifically the Sociosemiotics and the Semiotics of Cultures. As the works to be analyzed, one examined two traditional popular narratives, O Pavão do Mestre and O Soldado Jogador, each of them were collected both in oral tradition and in leaflets such as cordel like. The analysis took basis on the process of meaning in three stages of significance, such as: narrative, discursive and fundamental. One intended to collaborate for popular culture by studying its peculiarities. It is also important to emphasize that Paraíba is a place where this popular culture is mostly studied and considered as important craft for keeping a people s memory. Most of the times, one credits this attitude to UFPB which is a reknown institution held responsible for developing, analyzing and broadcasting the production of such historic, social and artistic manifestations.